195Pt and 15N NMR Data in Square Planar Platinum(II) Complexes of the Type [Pt(NH3)aXb]n (Xb = Combination of Halides): "NMR Effective Molecular Radius" of Coordinated Ammonia. Issue 35 (7th September 2020) - Benedetti, Michele; De Castro, Federica; Papadia, Paride; Antonucci, Daniela; Fanizzi, Francesco P.
Abstract : By studying a model set of square‐planar [Pt(NH3 ) a X b ] n ( a + b = 4; X b = combination of b halido ligands; n = 2 – b) complexes, we found that their δ ( 195 Pt) NMR chemical shift decreases proportionally to the platinum bonded halido ligands' ionic radii overall sum. This confirms also for these systems, the already observed NMR shielding attributed to pseudo ring currents, circulating around the M–X bond axis. Moreover, the present data show that also the NH3 ligands are characterized by a constant NMR shielding ability toward the central metal. This could be rationalized in term of a " NMR effective molecular radius " of the NH3 ligand, affecting the observed δ ( 195 Pt) as previously found for halido ligands. Interestingly, a δ ( 15 N) decrease is observed in Pt bonded NH3 ligands if the ionic radius of a cis halido ligand is increased. The opposite occurs if the ionic radius of a trans halido ligand is increased. The two contrasting effects stem from both shielding electric ring currents affecting the cis ligands and prevailing trans ‐influence due to coordinated halido ligands. Abstract : In the model [Pt(NH3 )3 X] + (X = Cl, Br, I) complex the red torus and arrows represent the electric pseudo ‐ring currents and the induced magnetic field, respectively, generated by an applied B° magnetic field. The considered Pt and cis to X N ‐donors are indicated in red instead the trans is in blue. Different colors represent opposite NMR chemical shift variations ( 195 Pt and 15 N) observed when the X ligand both ionic radius and trans ‐influence are varied. In this work, such considerations are extended to the general case of Pt II complexes with X and NH3 ligands.